Association of non-nutritive sweetener consumption with food craving and body image among university students: A cross-sectional study - Anfal AL-Dalaeen; Hebah Hamid; Tasneem Abu Hasan (PLoS ONE, 2025)
Non-nutritive sweeteners (NNS) are widely used for weight control and dietary regulation by university students, however, their psychological associations remain unclear. The aim of this study to investigate the associations between NNS consumption and food craving, and body dissatisfaction. A cross-sectional analysis was conducted among 300 students from Applied Science Private University (ASU) in Amman, Jordan. Participants completed a validated online questionnaire including demographic data, NNS consumption, food craving using Food Craving Questionnaire-Trait Rediced (FCQ-Tr), and perceptions of Sihhouette Ratine Scale Dissatisfcation index (SRS-D) body image using. To evaluate the associations between NNS exposure and psychological outcomes, age, sex, body mass index (BMI), dieting status, smoking behavior, were adjusted using multivariable linear and ordinal regression models. The NNS consumption was 83.3% among university students, with 30.0% indicating daily use of NNS. Increased frequency of NNS intake was significantly associated with higher FCQ-T-r scores (β = 0.21, 95% CI [0.08–0.34], p = 0.002) and elevated SRS-D scores (β = 0.17, 95% CI [0.05–0.29], p = 0.006). Also (74.3%) reported no mood change after NNS intake, and 21.0% reported mood enhancement. These findings found that frequent NNS = intake is associated with heightened food craving and body dissatisfaction among students, independent of body weight, age, smoking or academic faculty.